Estudo anatômico do lenho e descrição morfológica de cinco espécies sul-rio-grandenses da família Rhamnaceae - Santos, Sidinei Rodrigues dos (2008)
The family Rhamnaceae is little represented in Brazil and scarcely known with regard to its wood anatomical structure. It includes species with an extraordinary habit diversity and morphologic aspects with a tendency toward xeromorphism. The present study aims to investigate the wood anatomy, besides providing a morphologic descriptions of five native species: Colletia paradoxa (Sprengel) Escalante, Discaria americana Gillies et Hooker, Gouania ulmifolia Hooker et Arnott, Rhamnus sphaerosperma Swartz e Scutia buxifolia Reissek. Wood samples and used exsiccatae was gained in the wood collections and herbarium of the Forest Sciences Department, of the Federal University of Santa Maria, as well as of other herbaria in the state of Rio Grande do Sul and of own collection material. The terminology used in the botanical description followed Radford et al. (1974). The wood description followed the recommendations of Copant (1973), basically. Most part of the wood anatomical characteristics agrees with the common pattern in the family, including: non exclusively solitary pores; very short vascular elements, usually with short tails; only simple perforation plates; alternate intervessel pits, not vestured and with include openings; scarce paratracheal parenchyma, in non-stratefied series; heterogeneous type II rays, very numerous, non-stratified and non-exclusively uniseriate; and non-septate fibres, with simple pits in the walls. The presence of tails in vascular elements is reported for the first time to Rhamnaceae. The five studied species present enough anatomical particularities to its identification. The frequency and diameter of pores, as well as the vascular elements length, are apparently related to species growth habit. The predominant presence of specialized anatomical characteristics lend a developed character to the secondary xylem of the studied species. From the anatomical point of view, xeromorphic characteristics were also recognized in the wood. With regard to external morphology, it is not preferable the recognition of infra-specific categories in Rhamnus sphaerosperma Swartz, as proposed by Johnston (1978), due to overlapping of some morphologic characters used by the author, in order to separate its varieties. In Colletia paradoxa, in spite of the considerable variations in external branches morphology among some individuals, it is not recommended the recognition of different species, due to the similarity in reproductive structures.